Tenofovir alafenamide versus tenofovir disoproxil fumarate for the treatment of HBeAg-positive chronic hepatitis B virus infection: a randomised, double-blind, phase 3, non-inferiority trial. (November 2016) - Chan, Henry L Y; Fung, Scott; Seto, Wai Kay; Chuang, Wan-Long; Chen, Chi-Yi; Kim, Hyung Joon; Hui, Aric Josun; Janssen, Harry L A; Chowdhury, Abhijit; Tsang, Tak Yin Owen; Mehta, Rajiv; Gane, Edward; et al.
Summary: Background: Tenofovir alafenamide is a novel prodrug formulated to deliver the active metabolite to target cells more efficiently than tenofovir disoproxil fumarate at a lower dose, thereby reducing systemic exposure. In patients with HIV, tenofovir alafenamide was as efficacious as tenofovir disoproxil fumarate, with reduced bone and renal toxic effects. We compared the efficacy and safety of the two drugs in patients with HBeAg-positive chronic hepatitis B virus (HBV) infection in a non-inferiority study. Methods: We did this ongoing double-blind, non-inferiority study in 161 outpatient centres in 19 countries. Patients with chronic HBV infection who were positive for the hepatitis B e antigen (HBeAg) were randomly assigned (2:1) to receive either 25 mg tenofovir alafenamide or 300 mg tenofovir disoproxil fumarate with matching placebo. Randomisation was done by a computer-generated allocation sequence (block size six) stratified by plasma HBV DNA concentration and previous treatment experience. The primary efficacy endpoint was the proportion of patients with HBV DNA less than 29 IU/mL at week 48 in all patients who were randomly assigned and received at least one dose of study drug using a missing-equals-failed approach. The pre-specified non-inferiority margin was 10%. Key prespecified safety endpoints were bone and renal parameters at week 48. This study is registered withClinicalTrials.gov, numberNCT01940471 . Findings: Of the 1473 patients screened from Sept 11, 2013, to Dec 20, 2014, 875 eligible patients were randomly assigned and 873 received treatment (581 with tenofovir alafenamide and 292 with tenofovir disoproxil fumarate). 371 (64%) patients receiving tenofovir alafenamide had HBV DNA less than 29 IU/mL at week 48, which was non-inferior to the 195 (67%) of patients receiving tenofovir disoproxil fumarate who had HBV DNA less than 29 IU/mL (adjusted difference −3·6% [95% CI −9·8 to 2·6]; p=0·25). Patients given tenofovir alafenamide had a significantly smaller decrease in bone mineral density at hip (mean change −0·10% [95% CI −0·29 to 0·09] vs −1·72% [–2·02 to −1·41]; adjusted difference 1·62 [1·27 to 1·96]; p<0·0001) and at spine (mean change −0·42% [–0·66 to −0·17] vs −2·29% [–2·67 to −1·92]; adjusted difference 1·88 [1·44 to 2·31]; p<0·0001) as well as smaller mean increases in serum creatinine at week 48 (0·01 mg/dL [0·00–0·02] vs 0·03 mg/dL [0·02–0·04]; p=0·02). The most common adverse events overall were upper respiratory tract infection (51 [9%] of 581 patients receiving tenofovir alafenamide vs 22 [8%] of 292 patients receiving tenofovir disoproxil fumarate), nasopharyngitis (56 [10%] vs 16 [5%]), and headache (42 [7%] vs 22 [8%]). 22 (4%) patients receiving tenofovir alafenamide and 12 (4%) patients receiving tenofovir disoproxil fumarate experienced serious adverse events, none of which was deemed by the investigator to be related to study treatment. 187 (32%) of 581 patients in the tenofovir alafenamide group and 96 (33%) of 292 patients in the tenofovir disoproxil fumarate group had grade 3 or 4 laboratory abnormalities, the most common of which were elevations in ALT (62 [11%] of 577 patients receiving tenofovir alafenamide and 36 [13%] of 288 patients receiving tenofovir disoproxil fumarate) and AST (20 [3%] of 577 patients receiving tenofovir alafenamide and 19 [7%] of 288 patients receiving tenofovir disoproxil fumarate). Interpretation: In patients with HBeAg-positive HBV infection, tenofovir alafenamide was non-inferior to tenofovir disoproxil fumarate, and had improved bone and renal effects. Longer term follow-up is needed to better understand the clinical impact of these changes. Funding: Gilead Sciences.